KARDIOCHIRURGIA DOROSŁYCHIntraoperative treatment of atrial fibrillation – progressing from scalpel to laser - Olasińska-Wiśniewska, Anna; Mularek-Kubzdela, Tatiana; Grajek, Stefan; Sarnowski, Wojciech; Jemielity, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Atrial fibrillation is the most frequent supraventricular tachyarrhythmia. It considerably impairs patients’ quality of life and constitutes a significant risk for thromboembolic complications, including stroke, heart failure, tachyarrhythmic cardiomyopathy and death. Contemporary treatment of atrial fibrillation is based on pharmacotherapy, electrical cardioversion, and percutaneous and intraoperative ablation. In patients with atrial fibrillation and mitral valve disease, valvular surgery alone rarely restores sinus rhythm. That is why it is so important to use antiarrhythmic techniques in surgical treatment of mitral valve disease. Since Cox’s first procedures, the methods of intraoperative treatment of atrial fibrillation have undergone a number of modifications both with regard to application lines and the source of energy used. This article presents a short synthesis of achievements to date in the field of surgical treatment of atrial fibrillation, including factors which may influence the efficacy of the procedure.